On teaching of Persian language in Armenian schools of Iran in the second half of the 19th century and the first half of the 20th century - Tereza Amryan (Banber Arevelagitut'yan Instituti, 2023)
In the article, the activities of Armenian schools in Iran in the second half of the 19th century and the first half of the 20th century, and the teaching of the Persian in those schools are addressed. The purpose of the study is to examine the teaching of Persian in Armenian schools․ For conducting the research historical and comparative-historical methods have been used․ In the second half of the 19th century and at the beginning of the 20th century the Armenian schools of Iran were influenced by the Armenian schools of the Caucasus. They often brought educational literature from Tbilisi to Iran and sometimes invited teachers from there. Along with foreign languages, Persian was also taught at Armenian schools in Iran. During the years of the constitutional movement, the classes of Persian language became more widespread in Armenian schools. During the reign of Reza Shah, the management of all schools in the country came under the control of the state, and the teaching of Persian became mandatory in all schools. Thus, in the second half of the 19th century the teaching of Persian facilitated the integration of students into economic and social life, but after educational reforms and standardization of school curriculum, the teaching of Persian gradually became mandatory and standardized in all Armenian schools of Iran.